Pemanfaatan Web Gis Dalam Sistem Informasi Pemasaran Rumah Kredit BNI Jombang - Lailia Rahmawati; Yuniar Adam De Hilma; Winarti (Bulletin of Information Technology (BIT), 2022)
Bank Negara Indonesia (Persero) Tbk or BNI is one of the oldest commercial banks in the history of the State of Indonesia. This bank was established on July 5, 1949 as the central bank and in 1968, BNI was designated as “Bank Negara Indonesia 1946”, and its status became a State-Owned Commercial Bank. The house is one of the most important needs for the community. The difficult economic conditions and the many demands that must be met by the community make the bank as a place for people to own a house on credit, especially for people with middle to lower economic levels. Buying a house on credit among the public is a very attractive option. The purpose of marketing is to understand the wants and needs of consumers so that the product or service can sell itself. In marketing their products, a marketer must be good at reading the market situation now and in the future. This means that marketers must be responsive to what consumers want and need. Therefore, marketing is needed. If the bank still acts passively, it is possible that the banking service product will not be recognized by the public. These marketing activities are proposed to maintain the existence of banking in the hearts of customers or prospective customers. Therefore, from marketing activities, customers or other prospective customers can obtain accurate information about housing provided by a BNI Jombang bank